The Effect of Goal Setting and Mental Imagery Intervention on Badminton Learning Achievement Motor Skill at 10-12 Years Old: The Context of Indonesia - Hidayat, Yusup (EDUCARE, 2011)
ABSTRACT: The purpose of this research was to examine the influence of goal setting and mental imagery as two methods of psychological skill training on learning achievement of badminton motor skill. Fifty beginning female athletes at 10-12 years old (M = 10.8) from Bandung FPOK UPI Badminton School were divided into four experimental groups and one control group in random. Before getting the treatment, all groups carried out motor ability test, then all experimental groups were given following instructional about goal setting, mental imagery training, and badminton motor skill materials according to experimental condition in each group. It was hypothesized that shifting goal would more improve the development of high service and defensive clear skill than process goal, and mental imagery training would more enhance high service and defensive clear skill than without mental imagery training. The result of data computation by two ways factorial ANCOVA showed that goal setting and mental imagery training method given a significant main effect, but no interaction both of them. Furthermore, the result of means adjusted pair comparison analysis indicated that the effectiveness of mental imagery training influenced by goal setting but not vice versa. Mental imagery process of the mental imagery training group was significantly higher than without mental imagery training, and all experimental groups have a significantly learning achievement higher than control group. KEY WORDS: Psychological skill training method, goal setting, mental imagery, learning achievement, badminton motor skill.About the Author: Dr. Yusup Hidayat is a Lecturer at the School of Health and Physical Education UPI (Indonesian University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: yusuf_h2000@yahoo.com and indrahafizh@yahoo.co.idHow to cite this article? Hidayat, Yusup. (2011). âThe Effect of Goal Setting and Mental Imagery Intervention on Badminton Learning Achievement Motor Skill at 10-12 Years Old: The Context of Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.3(2) February, pp.129-144. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 15, 2010); Revised (January 15, 2011); and Published (February 17, 2011).